QTL analysis for sodium removal ability in rice leaf sheaths under salinity using an IR-44595/318 F2 population - Goto, Itsuki; Neang, Sarin; Kuroki, Ryuichi; Reyes, Vincent Pamugas; Doi, Kazuyuki; Skoulding, Nicola Stephanie; Taniguchi, Mitsutaka; Yamauchi, Akira; Mitsuya, Shiro (Frontiers in Plant Science, 2022)
Over-accumulation of salt in rice plants is an effect of salt stress which decreases growth and grain yield. Salt removal ability in leaf sheaths is a tolerance mechanism to decrease salt entry and accumulation in leaf blades and maintain photosynthesis under salinity. In this study, a QTL analysis of removal ability of sodium ions (Na+) in leaf sheaths and Na+ accumulation-related traits, was conducted using F2 population between two rice varieties, IR-44595 with superior Na+ removal ability, and 318 with contrasting Na+ removal ability in leaf sheaths under salinity. Suggestive QTLs for Na+ removal ability in leaf sheaths were found on chromosomes 4 and 11. The suggestive QTL on chromosome 11 overlapped with other significant QTLs for Na+ concentration in shoots, leaf blades and leaf sheaths, and Na+/K+ ratio in leaf blades. Correlation analysis indicated that Na+ removal ability in leaf sheaths is important in reducing Na+ accumulation in leaf blades. The varietal difference of Na+ removal ability in leaf sheaths at the whole plant level was greater at lower NaCl concentrations and became smaller as the treatment NaCl concentration increased. Although the Na+ removal ability in leaf sheath was comparable between IR-44595 and 318 under high salinity at the whole plant level, the younger leaves of IR-44595 still showed a higher Na+ sheath-blade ratio than 318, which implied the Na+ removal ability functions in the younger leaves in IR-44595 to reduce Na+ entry in young leaf blades even under high salinity.